Horizontal and vertical equity and public subsidies for private health insurance in the U.S - Jacobs, Paul D.; Hill, Steven C. (Social science & medicine (1982), 2024)
The United States offers two markedly different subsidy structures for private health insurance. When covered through employer-based plans, employees and their dependents benefit from the exclusion from taxable income of the premiums. Individuals without access to employer coverage may obtain subsidies for Marketplace coverage. This paper seeks to understand how the public subsidies embedded in the privately financed portion of the U.S. healthcare system impact the payments families are required to make under both ESI and Marketplace coverage, and the implications for finance equity. Using the Household Component of the Medical Expenditure Panel Survey (MEPS-HC) and Marketplace premium data, we assess horizontal and vertical equity by calculating public subsidies for and expected family spending under each coverage source and using Lorenz curves and Gini and concentration coefficients. Our study pooled the 2018 and 2019 MEPS-HC to achieve a sample size of 10,593 observations. Our simulations showed a marked horizontal inequity for lower-income families with access to employer coverage who cannot obtain Marketplace subsidies. Relative to both the financing of employer coverage and earlier Marketplace tax credits, the more generous Marketplace premium subsidies, first made available in 2021 under the American Rescue Plan Act, substantially increased the vertical equity of Marketplace financing. While Marketplace subsidies have clearly improved equity within the United States, we conclude with a comparison to other OECD countries highlighting the persistence of inequities in the U.S. stemming from its noteworthy reliance on employer-based private health insurance. •United States uses employer and individual private health insurance coverage.•No recent investigations of horizontal and vertical equity of U.S. private coverage.•Analysis of Gini coefficients and Lorenz curves suggests regressivity.•Public policies including insurance subsidies can reduce inequities.